Malaysian path to sustainable development: transitions to sustainability - Abdul Samad Hadi,; Shaharudin Idrus,; Abdul Hadi Harman Shah,; Ahmad Fariz Mohamed, (Environmental Management Society, Malaysia, 2011)
This article discusses the development path taken by Malaysia after Independence to achieve a developed country status by the year 2020, from pursuing economic development with redistribution paying somewhat little attention to the health of the environment to a balanced approach through a balanced development strategy involving the pursuance of economic growth, societal development and protecting the natural as well as the built-up environment. And then in April 2010 the Malaysian Prime Minister announced to the Malaysian public the concept and substance of the New Economic Model (NEM) that will leverage future Malaysian development efforts. In the NEM, economic growth is still a pivotal concern but this time with a difference to similar efforts to achieve economic growth in the past, in that economic growth in the NEM is to push Malaysia into a higher income country, thus freeing the country from the middle income syndrome. The average Malaysians will enjoy in the end living in a peaceful, prosperous and livable country captured in a living condition of a high quality of life. In short, for over fifty years after Independence Malaysia has experienced two development phases, and now entering into another one- a third one, forming in all three transitions to sustainability. What have been the environmental impacts of those development phases to the country and the Malaysian citizen? During the period of growth with redistribution, the economy was making the country a reasonably comfortable country with a rising middle class but poverty was still ravaging, and the environment was slowly degrading. There was a conscious effort by the government to conserve bio-diversity and protect the environment during the sustainable development phase; but the momentum of pursuing growth and societal development the environment continued to experience degradation. It is too soon to evaluate the fate of the environment in the NEM phase. But the fact that economic activities for high growth, social ‘inclusivity’ as the second pillar with sustainability as the third pillar the way forward for the environment seems well protected to deliver the promised higher and better quality of Malaysian life in the future.